2018
DOI: 10.1177/1087054718787891
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Reciprocal Relations Between ADHD symptoms and Emotional Problems in School-Age Children

Abstract: Our findings highlight the transactional and dynamic interplay between inattention symptoms and emotional problems and support the mechanistic role of inattention symptoms in the development and persistence of emotional problems in school-age children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Symptoms of emotional distress in children (e.g., irritability, sadness, and worry) are frequently accompanied by externalizing behaviors (e.g., restlessness, temper tantrums, and inability to concentrate) and may even predict attention-deficit/hyperactivity disorder (ADHD) symptoms over time ( Brocki et al, 2019 ). In fact, recent studies have suggested that emotional problems may positively predict inattention symptoms and that high levels of physical (e.g., headaches and stomachaches) and internalizing symptoms – associated with emotional distress – are typically present before a diagnosis of ADHD ( Han et al, 2020 ). Both internalizing and externalizing symptoms in children and preadolescents can have serious consequences for their interpersonal, cognitive, and psychological domains, such as impaired social competency, substance abuse, poor academic performance, and decreased mental health ( Creavey et al, 2018 ; Gargano et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms of emotional distress in children (e.g., irritability, sadness, and worry) are frequently accompanied by externalizing behaviors (e.g., restlessness, temper tantrums, and inability to concentrate) and may even predict attention-deficit/hyperactivity disorder (ADHD) symptoms over time ( Brocki et al, 2019 ). In fact, recent studies have suggested that emotional problems may positively predict inattention symptoms and that high levels of physical (e.g., headaches and stomachaches) and internalizing symptoms – associated with emotional distress – are typically present before a diagnosis of ADHD ( Han et al, 2020 ). Both internalizing and externalizing symptoms in children and preadolescents can have serious consequences for their interpersonal, cognitive, and psychological domains, such as impaired social competency, substance abuse, poor academic performance, and decreased mental health ( Creavey et al, 2018 ; Gargano et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Chinese SNAP-IV has been widely used in assessing ADHD and ODD symptoms in clinical and research settings in Taiwan (e.g. (Chiang et al ., 2015; Han et al ., 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has indicated reciprocal linkage of (some of) the domains included in the SDQ: A one-year longitudinal study with four waves including both children and adolescents showed that emotional problems (as measured by the SDQ) and ADHD symptoms of inattention and hyperactivity/impulsivity are linked (Han et al, 2020). In their study, Han and colleagues (2020) found that inattention symptoms were transactionally and dynamically related to emotional problems, whereas hyperactivity/impulsivity and emotional problems were related, but not reciprocally.…”
Section: Illustratory Example With the Longitudinal Millenium Cohort Studymentioning
confidence: 99%
“…Given that (i) scores on the SDQ have been shown to be predictive of an increased risk in psychopathology of children and adolescents (Becker et al, 2015) and (ii) studies highlighting the (reciprocal/causal) relations between dimensions of the SDQ (e.g., Han et al, 2020), we will be applying the aforementioned statistical framework to longitudinal assessments of the SDQ dimensions (3-to 7-year-olds; 3 waves) of two groups: normally developing children (N = 7333) and children who have long lasting (12 months or more) social/ behavioral problems, such as ADHD, autism or Asperger's Syndrome at age 14 (N=290). As this analysis primarily serves as an illustratory example of the proposed networks of developmental dynamic parameters, we refrain from any confirmatory testing.…”
Section: Illustratory Example With the Longitudinal Millenium Cohort Studymentioning
confidence: 99%